Improving The Quality of Sweet Duck Jerky from South Kalimantan through Modification of Antioxidant-Rich Spices - H. Kurniawan; T. Suryati; A. Apriantini (Department of Animal Production and Technology, Faculty of Animal Science, IPB University in associated with Animal Scientist's Society of Indonesia (HILPI), 2023)
Various processed duck meat generally still uses rejected duck meat. The weakness of rejected duck meat is its tough texture, fishy smell, and high-fat content. Fat content increases the possibility of lipid oxidation and the formation of free radicals. The effort to overcome this is by adding antioxidant-rich spices during processing, one of which is sweet duck jerky from South Kalimantan. The research aimed to analyze the effect of modification of antioxidant-rich spices and obtaining the best spice formula in the manufacturing process. The study used a 3x3 factorial completely randomized design (CRD) with three replications. First factor was three different spice formula (formula A, formula B, and formula C), and the second factor was three different storage times (0 week, two weeks, and four weeks). Data were analyzed using analysis of variance, and significant results were then tested using the Tukey test. The results showed that the spice formula had a significant effect (p<0.05) on malondialdehyde (MDA) content, DPPH inhibition, and antioxidant capacity. There was an interaction between spice formulas and storage times on microbiological characteristics, MDA content, DPPH inhibition, and antioxidant capacity. The study concludes that the modification of spices increases the quality of duck jerky, especiallyfrom antioxidant activity and ability to maintain low MDA content. B spice formula showed the best formula than other spice formulas.